Pengertian, Ruang Lingkup Manajemen, dan Kepemimpinan Pendidikan Islam - Juhji, Juhji; Wahyudin, Wawan; Muslihah, Eneng; Suryapermana, Nana (Program Studi S3 Pascasarjana Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, Indonesia, 2020)
This paper was written aimed at explaining the understanding of management, scope of management, and leadership of Islamic education. The writing method uses Ms. Word and journal templates. Zotero applications are used for citations and APA 7th (American Psychological Association 7th edition) as a reference style. The paper discussion data is obtained from primary and secondary data derived from international and nationally reputable books and journals. The results of the paper suggest that management activities cover a broad spectrum, starting from activities on how to determine the direction of the organization in the future, creating organizational activities, encouraging cooperation between fellow members of the organization, and overseeing activities in achieving the goals. Islamic education leadership is a leadership process in Islamic education to move, influence, motivate, and direct people within educational institutions to achieve the goals that have been formulated.